A SUGGESTED SYLLABUS FOR THE COURSE ‘INTRODUCTION TO BRITISH LITERATURE I’ AT ELT DEPARTMENTS - Nazlı Gündüz (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Students at English Language Teaching Departments need to be guided into appreciating British literature and ‘Introduction to British Literature I’ has to introduce the learners with the major genres of literature such as poetry, prose and drama, as well as, the culture and language of the British nation. This study has mainly been conducted to offer a suggested syllabus for the course ‘Introduction to British Literature I’, a third term course at ELT departments of Education Faculties. Six lecturers and 266 students have contributed to the data collection. It not only investigates the current situation and syllabi in use through interviews with lecturers, but also the views, thoughts and needs of students through questionnaires conducted at ELT departments of several universities. In light of the results it offers an alternative definition to YÖK’s definition for the course, and a suggested syllabus with clear goals and objectives accompanied by a six-unit coursebook with course materials covering the course goals and objectives